2021
DOI: 10.1007/s00424-021-02639-7
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic activation of the epithelial sodium channel (ENaC) by factor VII activating protease (FSAP) and its relevance for sodium retention in nephrotic mice

Abstract: Proteolytic activation of the epithelial sodium channel (ENaC) by aberrantly filtered serine proteases is thought to contribute to renal sodium retention in nephrotic syndrome. However, the identity of the responsible proteases remains elusive. This study evaluated factor VII activating protease (FSAP) as a candidate in this context. We analyzed FSAP in the urine of patients with nephrotic syndrome and nephrotic mice and investigated its ability to activate human ENaC expressed in Xenopus laevis oocytes. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 44 publications
1
28
0
1
Order By: Relevance
“…Our study was inspired by these in vitro findings and aimed at clarifying the relevance of prostasin for the proteolytic ENaC activation in nephrotic syndrome in vivo. To date, our group has evaluated several serine proteases such as urokinase-type plasminogen activator (encoded by Plau ), plasminogen ( Plg ), plasma kallikrein ( Klkb1 ) or factor VII activating protease ( Habp2 ) with regard to their relevance for proteolytic ENaC activation in experimental nephrotic syndrome [ 4 , 8 , 20 , 36 ]. All of these activate ENaC in the Xenopus laevis -oocyte expression system by cleavage of the γ-subunit as evidenced by Western blot of cell surface expressed ENaC.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was inspired by these in vitro findings and aimed at clarifying the relevance of prostasin for the proteolytic ENaC activation in nephrotic syndrome in vivo. To date, our group has evaluated several serine proteases such as urokinase-type plasminogen activator (encoded by Plau ), plasminogen ( Plg ), plasma kallikrein ( Klkb1 ) or factor VII activating protease ( Habp2 ) with regard to their relevance for proteolytic ENaC activation in experimental nephrotic syndrome [ 4 , 8 , 20 , 36 ]. All of these activate ENaC in the Xenopus laevis -oocyte expression system by cleavage of the γ-subunit as evidenced by Western blot of cell surface expressed ENaC.…”
Section: Discussionmentioning
confidence: 99%
“…Active factor VII activating protease (FSAP) is excreted in urine of nephrotic patients and doxorubicin‐induced nephrotic mice, and found to activate ENaC in vitro in the Xenopus oocyte expression system 22 . However, in nephrotic FSAP‐deficient mice, the proteolytic cleavage pattern of α‐ and γ‐ENaC was similar to untreated animals and these mice were not protected from Na + retention, rendering it unlikely that this protease is responsible for proteolytic ENaC activation 3,22 …”
Section: Enac Regulation By Proteasesmentioning
confidence: 99%
“…29 In this review, we explore several F I G U R E 1 Structural schematic of identified ENaC CAPs. CAP1 (Prss8, prostasin), 4,5 CAP2 (Tmprss4), 6 CAP3 (St14/Matriptase), 6 Tmprss3, 7 Tmprss2, 8,9 uPA (urokinase-type plasminogen activator), 10,11 plasminogen, [12][13][14][15] trypsin, 16 chymotrypsin, 14 tissue 17,18 and plasma kallikrein, 19 elastase, 20 furin, 21 factor VII activating protease, 22 cathepsin B, 23,24 cathepsin S, 14 meprin β 25 and serralysin. 26 Predicted structural domains of mouse proteases are indicated 27 : CUB, complement C1r/C2s, urchin embryonic growth factor, bone morphogenic protein 1; EGF, epidermal growth factor-like; apple; kringle; GPI, glycophosphatidylinositol anchor; LDL-A, low density lipoprotein A; MAM, meprin, A5 protein, receptor protein phosphatase μ; MATH, meprin and TRAF-C homology; P/Homo B, paired basic amino acid residue-cleaving enzyme/homo sapiens B; PAN, PAN/apple; SEA, sperm protein, enterokinase and agrin; SRCR, scavenger receptor cysteine-rich; TM, transmembrane questions: how these proteases modulate ENaC function mechanistically, whether ENaC activation is dependent on its proteolytic cleavage, whether this proteolytic activity is essential in vivo and to which extent a loss-or gain-of-function of proteases in mice determines ENaCmediated Na + losing or retaining phenotypes.…”
mentioning
confidence: 99%
“…Knockout mouse models also allow to test the pathophysiological relevance of a candidate serine protease when there is evidence of an ENaC activating effect in vitro. For instance, plasma kallikrein or factor VII‐activating protease has been found to cleave γ‐ENaC at the prostasin cleavage in Xenopus laevis oocytes 116,117 . However, mice lacking these serine proteases were not protected from sodium retention after induction of experimental NS, arguing against an essential role of these proteases in vivo.…”
Section: Investigation Of Sodium Retention In Experimental Ns In Rodentsmentioning
confidence: 99%
“… 85 These results, however, point to the possibility of other serine proteases than the uPA‐plasminogen‐plasmin system contributing to ENaC activation. Other aprotinin‐sensitive proteases such as plasma kallikrein, 116 factor VII‐activating protease, 117 or prostasin 125 have been excluded as not essential for the proteolytic activation of ENaC in the DIN model. Further in vivo studies are required for a better understanding of the pathophysiological relevance of the exact serine protease or the interactions among serine proteases implicated in the proteolytic activation of ENaC in NS.…”
Section: Investigation Of Sodium Retention In Experimental Ns In Rodentsmentioning
confidence: 99%